The local, remote, and global consequences of climate feedbacks - Feldl, Nicole (2013)
Thesis (Ph.D.)--University of Washington, 2013 Climate feedbacks offer a powerful framework for revealing the energetic pathways by which the system adjusts to an imposed forcing, such as an increase in atmospheric CO 2 . We investigate how local atmospheric feedbacks, such as those associated with Arctic sea ice and the Walker circulation, affect both global climate sensitivity and spatial patterns of warming. Emphasis is placed on a general circulation model with idealized boundary conditions, for the clarity it provides. For this aquaplanet simulation, we account for rapid tropospheric adjustments to CO 2 and explicitly diagnose feedbacks (using radiative kernels) and forcing for this precise model set-up. In particular, a detailed closure of the energy budget within a clean experimental set-up allows us to consider nonlinear interactions between feedbacks. The inclusion of a tropical Walker circulation is found to prime the Hadley Circulation for a larger deceleration under CO 2 doubling, by altering subtropical stratus decks and the meridional feedback gradient. We perform targeted experiments to isolate the atmospheric processes responsible for the variability in climate sensitivity, with implications for high-sensitivity paleoclimates. The local climate response is characterized in terms of the meridional structure of feedbacks, atmospheric heat transport, nonlinearities, and forcing. Our results display a combination of positive subtropical feedbacks and polar amplified warming. These two factors imply a critical role for transport and nonlinear effects, with the latter acting to substantially reduce global climate sensitivity. At the hemispheric scale, a rich picture emerges: anomalous divergence of heat flux away from positive feedbacks in the subtropics; clear-sky nonlinearities that reinforce the pattern of tropical cooling and high-latitude warming tendencies; and strong ice-line feedbacks that drive further amplification of polar warming. These results have implications for regional climate ...